The Therapeutic Potential of Apitherapy: A Comprehensive Review on the Health Benefits of Honey and Propolis - Żak, Katarzyna; Madyniak, Katarzyna; Jucha, Hubert; Kluz, Agnieszka; Pliszka, Aleksandra; Mazur, Michał; Jarych, Weronika; Zukierski, Krystian; Michalak, Katarzyna (Quality in Sport, 2025)
Apitherapy has been developed in recent years, providing treatments using honey and other bee products to combat various diseases. Honey and propolis contain bioactive compounds such as flavonoids and phenolic acids, minerals, vitamins, enzymes and many more which are responsible for numerous health-promoting features. [1] Among this benefits are anti-diabetic, cardioprotective, wound healing, antiviral, antimicrobal, anti-aging, immunomodulatory effects. The purpose of this review is to summarize and update the current information regarding the role of honey and propolis in health and diseases. Aim of the study This study reviews recent research on honey and propolis, highlighting their key healing compounds and clinical applications in treating various diseases. The study proposes directions for future research and highlights knowledge gaps. Materials and methods To evaluate studies on the therapeutic effects of honey and propolis, we conducted a comprehensive literature review using databases, including PubMed, Google Scholar, and ScienceDirect. The main keywords used in the search included: apitherapy, honey, propolis. Conclusions In conclusion, honey and propolis are emerging as promising therapeutical options, with evidence supporting their effectiveness in treating various health conditions (cardiovascular diseases, prediabetes, hypertension, infections, pain, and wound healing). Given their safety, efficacy, and inexpensiveness, they could be viable alternatives to conventional treatment. However, further research is crucial to better understand the active ingredients and mechanisms of action, ultimately guiding the development of effective therapies and clear clinical guidelines.